2000
DOI: 10.1177/004051750007000804
|View full text |Cite
|
Sign up to set email alerts
|

Applying Fuzzy Logic and Neural Networks to Total Hand Evaluation of Knitted Fabrics

Abstract: This study of two new total hand simulating methods for knits uses fuzzy theory and neural networks. One method, a neural network system trained with a back-propaga tion algorithm, performs functional mapping between mechanical properties and the resulting total hand values of the fuzzy predicting method. The second method, a fuzzy-neural network system, uses the fuzzy membership function, weighted factor vector, and error back-propagation algorithm. The principal mechanical properties of stretchiness, bulkine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 14 publications
0
35
0
3
Order By: Relevance
“…In the validation, the results show that the proposed network also predicts the hand of linen and silk. Another work for predicting fabric hand from physical measures has been done by combining fuzzy logic and neural networks (Park et al, 2000). The obtained results revealed that the neural networks and fuzzy logic provide an alternative approach for predicting sensory properties from instrumental measurements of fabrics.…”
Section: Modeling the Relationship Between Sensory Properties And Insmentioning
confidence: 99%
“…In the validation, the results show that the proposed network also predicts the hand of linen and silk. Another work for predicting fabric hand from physical measures has been done by combining fuzzy logic and neural networks (Park et al, 2000). The obtained results revealed that the neural networks and fuzzy logic provide an alternative approach for predicting sensory properties from instrumental measurements of fabrics.…”
Section: Modeling the Relationship Between Sensory Properties And Insmentioning
confidence: 99%
“…The prediction of the fabric hand is a complex, highly non-linear problem and therefore an early target for the application of ANNs (Youssefi & Faez, 1999;Hui et al, 2004;Shyr et al, 2004;Matsudaira, 2006). The data from the FAST system were used to approach the hand of the fabrics (Sang-Song & Tsung- , while fuzzy logic has been combined with ANN for the evaluation of the fabric hand (Park et al, 2000;Park et al, 2001). ANNs in combination with fuzzy logic have been used in the case of the prediction of the sensory properties of the fabrics, as well (Jequirim et al, 2009).…”
Section: Fabricsmentioning
confidence: 99%
“…Some research has therefore explored the relationship between objective and sensory fabric hand evaluations (Hu et al 1993;Park et al 2000). However, we consider that sensory and objective evaluations are two complementary information sources on a FHE and there certainly some information is lost if we replace one by the other.…”
Section: Integration Of Human and Machine Measurementsmentioning
confidence: 99%